Retrospective Analysis of Permafrost Landscape Evolution in Yakutia during the Holocene Warm Intervals - Alexander N. Fedorov; Varvara A. Novopriezzhaya; Nikolay A. Fedorov; Pavel Y. Konstantinov; Vera V. Samsonova (Land, 2020)
The observed global warming has significant impacts on permafrost. Permafrost changes modify landscapes and cause damage to infrastructure. The main purpose of this study was to estimate permafrost temperatures and active-layer thicknesses during the Holocene intervals with significantly warmer-than-present climates—the Atlantic (5500 years BP), Subboreal (3500 years BP) and Subatlantic (1000 years BP) optimums. Estimates were obtained using the ready-to-use models derived by G.M. Feldman, as well as mathematical modeling taking account of the paleogeography of the Holocene warm intervals. The data obtained were analyzed to reveal the regional patterns of warming impacts on different permafrost landscapes. The study results will be useful in predicting future permafrost changes in response to climate warming.